malB region in Escherichia coli K-12: specialized transducing bacteriophages and first restriction map. - Marchal, C (1978)
By starting from an Escherichia coli K-12 strain with a lambda phage integrated in the malB region, series of transducing phages carrying part or all of the malB region have been isolated. Genetic mapping of the transduced malB fragments was accomplished by complementation and recombination with known mutations in the region. By using the DNA of these phages, it was found that the malB region is cleaved by the restriction enzymes BglII, EcoRI, HaeII, HincII, SalI, and SstI, but not BamHI, HindIII, KpnI, PstI, XbaI, or XhoI. A physical map was constructed and tentatively correlated with the genetic map.